Implementasi Pembelajaran PKn dalam Menumbuhkan Rasa Cinta Siswa terhadap Budaya Lokal Begibung di Kelas IV MI Riadhussolihin Tohir Yasin - Haeratun Umi; Hilmiati; Syudirman (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study is motivated by the importance of fostering students’ love for local culture amid the increasing influence of external cultures. Civic Education (Civics) learning can serve as a means to introduce and instill local cultural values, one of which is the Begibung culture, which embodies the values of togetherness, mutual cooperation, unity, and tolerance. This study aims to determine the implementation of Civics learning in fostering students’ love for the local Begibung culture and the challenges faced by teachers in integrating it in Grade IV at MI Riadhussolihin Tohir Yasin. This research uses a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The results show that the implementation of Civics learning based on Begibung culture is carried out through the stages of planning, implementation, and evaluation of learning. Teachers integrate Begibung values into materials on cooperation, unity, and togetherness, thereby fostering students’ interest, awareness, appreciation, and pride in local culture. The challenges encountered include limited learning media and resources, students’ low understanding of Begibung cultural values, limited instructional time, and the influence of external cultures. Nevertheless, Civics learning based on Begibung culture has contributed to fostering students’ love for local culture.